2016
DOI: 10.1002/lary.26231
|View full text |Cite
|
Sign up to set email alerts
|

To image or not to image? A cost-effectiveness analysis of MRI for patients with asymmetric sensorineural hearing loss

Abstract: 2c. Laryngoscope, 127:939-944, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Asymmetry can be based on the average interaural difference (ID) of specific audiometric frequencies or a frequency range, the value of the maximum difference in one or more frequencies, or a combination of characteristics. Many different approaches have been documented (Cahani et al, 1984, Caldera and Pearson, 2000, Cheng and Wareing, 2012, Hendrix et al, 1990, Hojjat et al, 2017, Jeffery et al, 2016, Mangham, 1991, Margolis and Saly, 2008, National Guideline Centre UK, 2018, Tsai et al, 2012, Urben et al, 1999. Examples from clinical practice also differ.…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetry can be based on the average interaural difference (ID) of specific audiometric frequencies or a frequency range, the value of the maximum difference in one or more frequencies, or a combination of characteristics. Many different approaches have been documented (Cahani et al, 1984, Caldera and Pearson, 2000, Cheng and Wareing, 2012, Hendrix et al, 1990, Hojjat et al, 2017, Jeffery et al, 2016, Mangham, 1991, Margolis and Saly, 2008, National Guideline Centre UK, 2018, Tsai et al, 2012, Urben et al, 1999. Examples from clinical practice also differ.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium-enhanced nuclear magnetic resonance imaging (MRI) is the current diagnostic gold standard for retrocochlear lesions [ 5 , 21 ]. However, because the number of MRI exams needed on this group of patients is very large, and the number of schwannomas found is very small, screening algorithms have been developed to preserve and maximize resources [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 40% of these otologists stated that medicolegal concerns were a significant factor in their decision to pursue imaging. 17 Many studies [18][19][20][21] have suggested a non-contrast MRI with a dedicated IAC protocol to be used as an initial screening test for patients with SNHL. Sequences like T2-weighted imaging and a steady-state free precession (brand names "FIESTA," "TrueFISP," and balanced FFE) provide higher spatial resolution and clearer depiction of tiny intracranial structures.…”
Section: Introductionmentioning
confidence: 99%